Approaches to Islamic Art in the Museums: A Critical Review on Islamic Art and The Museum; Approaches to Art and Archaeology of the Muslim World in the Twenty-First Century - Masoumeh Karimi; Kouros Samanian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
It is about a half-century since the intellectual foundations of the concept of Islamic art have been dramatically challenged. This new trend has been culminated after the end of the colonial era, setting the stage for the spread of Islamic thought, the consequent establishment of Islamic Art museums in the West, and later, through the September 11 attacks. Simultaneously, the museology became a beneficial approach towards the study of the arts of Islamic regions through which the museum plays a crucial role in creating the knowledge of Islamic Art. Published in 2012, Islamic Art and the Museum; Approaches to Art and Archeology of the Muslim World in the Twenty-First Century was the first in this area. Using content analysis and taking a muselogical view, the current study recognizes the main approaches towards the representation of Islamic Art in American and European museums. The results show that although it is a worthwhile source with main challenges included, it can be criticized in terms of its fundamental approach towards the museum, the hegemony of historiographical point of view, the problematic relationship between some articles and titles, and its emphasis on one or two geographical areas.